Impact of vitamin D supplementation on post-stroke rehabilitation outcomes: A systematic review and meta-analysis - Murbawani, Etisa A.; Pramukarso, Dodik T.; Muis, Siti F.; Pudjonarko, Dwi; Subagio, Hertanto W.; Tjandra, Kevin C.; Respati, Danendra RP.; Nugraha, Laksmana AK.; Ramadhany, Ghifarie A.; Pranoto, Stephano (Narra J, 2025)
Each year, there are approximately 12.2 million new stroke cases and 6.5 million stroke-related deaths, with low- and middle-income countries shouldering a disproportionately high financial burden. Studies have associated vitamin D deficiency with arteriosclerosis, left ventricular hypertrophy, and vascular dysfunction, contributing to an elevated risk of stroke. The aim of this study was to evaluate how vitamin D supplementation affects post-stroke outcomes. A comprehensive literature search was performed across PubMed, Scopus, the Cochrane Library, ScienceDirect, Springer Link, ProQuest, and Epistemonikos from April to May 2024. This study focused on comparing the efficacy of vitamin D supplementation versus no supplementation in stroke patients of all ages. Outcome measures included the Functional Ambulation Classification (FAC), Brunnstrom Recovery Stage (BRS), Modified Rankin Scale (mRS), and National Institutes of Health Stroke Scale (NIHSS). Case reports, reviews, and research on other cardiovascular or metabolic issues were excluded. Five authors extracted data and analyzed bias separately using the Risk of Bias Version 2 (RoB V2) algorithms. The results of continuous variables were pooled into the mean difference (MD) along with 95% confidence intervals (CI) using random-effect models. Review Manager 5.4 was used to evaluate the data. Out of the 1,152,449 papers evaluated, six met the inclusion criteria, with a sample size ranging from 42 to 123 patients. Vitamin D supplementation was found to yield better outcomes after stroke. BRS in lower extremities showed better results (MD: 0.59 (95%CI: 0.27–0.91)), NIHSS improved with an MD of -1.47 (95%CI: -2.03–(-0.90)). Furthermore, there was also an improvement in mRS, with an MD of -0.91 (95%CI: -1.25–(-0.56)). In conclusion, vitamin D improved post-stroke outcomes, which supported its supplementation as a part of stroke rehabilitation.